Transplantation of human bodies and tissues: the bases of legal status of donor and recipient - Vasilevich, Grigory A.; Vasilevich, Dmitry G. (Journal of the Belarusian State University. Law, 2019)
The legal regulation of relations concerning the transplantation of human organs and tissues is analyzed. Belarus occupies one of the first places among the CIS countries in terms of the number of organ transplants. Its successes are also visible in the European space. In society, the positive value of transplantation of human organs and tissues is increasingly recognized for prolonging the life and work capacity of people. The article draws attention to the fact that there are four main subjects of the relationship concerning organ transplantation: donor (living and dead person); those close to him; the recipient; establishment of health care. The analysis of the legal status of each of these subjects is carried out. The circle of persons who can be living and dead donors according to the current legislation is analyzed. Attention is focused on the norms of international documents in this field of relations, the peculiarities of the legislation of foreign countries, including the attitude to the presumption of consent to the removal of organs for the purposes of donation. The number of proposals have been made to improve the current legislation. A proposal was made to expand the circle of relatives who can be living donors, in particular, it would be better to rely on relatives who may be heirs taking into account the existing queues of the heirs. One of the main principles of transplantation is «free». Therefore, widening the circle of living donors should not lead to a violation of this principle. It is proposed in the Belarusian law to provide that foreigners permanently residing in Belarus have the right to organ transplant. The Unified Registry of Transplantation should contain information not only about living individuals who have been seized by organs, but also of dead persons. Such transparency should help strengthen the rule of law in this area of relations.
Keywords: transplantation; living donor; dead donor; presumption of consent to removal of organs